School EFL Teachers’ Research Identity Construction in the Chinese University–School Community - Wang, Xuemei; He, Yanhua (Frontiers in Psychology, 2022)
Despite a relatively large number of studies on teachers’ identity development in the university-school community, few studies have focused specifically on school EFL teachers’ professional identity construction in their research life. This study adopts the Activity Theory and examines three school EFL teachers from three middle schools in China embedded in the University-School community, and investigates how three teachers constructed their professional identity about research and what factors influenced the development of their identities within the University-School activity system from both school and university teacher’s view. Data are collected by narratives and semi-structured interviews triangulated by documents such as meeting minutes and then analyzed by NVivo 12 qualitative analysis software. The findings of this study show that 1) the University-School collaborative program helps form a University-School community including both teaching and research; 2) in this community, EFL teachers continuously construct their identities from “practitioner” to “researcher”, and to “practitioner” again; 3) it highlights the internal factors comprising the research experience and the stage of career and the external factors including the curriculum reform context and the communication in the community. The findings carry important implications for school EFL teachers’ professional identity construction concerning their research life and teachers’ professional development in the University-School cooperation.